A review on the avoidance and evasion of income tax by urban unorganized sector of Punjab, India - Sharma, Kirti; Arora, Jyoti (Gyan Management Journal, 2022)
Taxes are major source of revenue to the government. Tax evasion and  avoidance are pervasive in all countries and which hampers the economic  development to greater extent. The present research brings out the issue that  integrate avoidance and evasion by the urban unorganised sector of Punjab  state which consist of workers or professionals who neither have registration  number nor monitored by government directly. To meet the objective, the  require data it is collected from primary as well as secondary sources which  are collected from 50 respondent which cover the aspect relevant to income  factor, total revenue, tax payment or non-payment related to prescribed  sector. This review paper focuses on highlighting the cause and ill effect of  tax evasion by unorganised sector which hinders the overall development  of state and country and finding the relevant measure which the tax  administration authorities can strategically and efficiently apply to combat  with the tax evasion in income tax by the unorganised sector.
Keywords: Economy; Integrate; revenue; Workers; Income tax